2021
DOI: 10.1186/s12889-021-10636-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of sleep duration with physical fitness performance and self-perception of health: a cross-sectional study of Taiwanese adults aged 23–45

Abstract: Background The relationship between sleep duration and physical fitness is one aspect of sleep health. Potential factors associated with sleep duration interfere with physical fitness performance, but the impact trends on physical fitness indicators remain unclear. Methods This study examined associations between sleep duration and physical fitness among young to middle-aged adults in Taiwan. A total of 42,781 Taiwanese adults aged 23–45 participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition, it has been reported that napping normalizes sleep loss-induced biochemical disruption [ 34 ]. Thus, daytime napping could be related with physical fitness due to sleep, and oxidant status is an important factor for physical fitness [ 12 , 35 ]. However, the explanation that links daytime napping and physical fitness in university students is different from that in athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that napping normalizes sleep loss-induced biochemical disruption [ 34 ]. Thus, daytime napping could be related with physical fitness due to sleep, and oxidant status is an important factor for physical fitness [ 12 , 35 ]. However, the explanation that links daytime napping and physical fitness in university students is different from that in athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The pressure of independent living and busy schoolwork may result in lack of time for physical activity [ 9 ], which may lead to the physical fitness status remaining stagnant or even declining. In addition to the direct effects of physical activity, other approaches have been linked to physical enhancement, such as nutrition [ 10 ], dietary habits [ 11 ], and sleep habits [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The examiner instructs participants to bend body slowly and records the maximum distance reached by their fingertips in cm. [12]…”
Section: Materials and Methodologymentioning
confidence: 99%